Some moment results about the limit of a martingale related to the supercritical branching random walk and perpetuities - Iksanov, О.М. (Український математичний журнал, 2006)
Let M(n),n=1,2,..., be the supercritical branching random walk in which the family sizes may be infinite with positive probability. Assume that a natural martingale related to M(n), converges almost surely and in the mean to a random variable W. For a large subclass of nonnegative and concave functions f , we provide a criterion for the finiteness of EWf(W). The main assertions of the present paper generalize some results obtained recently in Kuhlbusch’s Ph.D. thesis as well as previously known results for the Galton-Watson processes. In the process of the proof, we study the existence of the f-moments of perpetuities. Нехай M(n),n=1,2,..., — надкритичне випадкове блукання, у якому розмір родини може бути нескінченним з додатною ймовірністю. Припустимо, що стандартний мартингал, пов'язаний з M(n), збігається майже напевно і в середньому до випадкової величини W. Для великого підкласу невід'ємних та вгнутих функцій f наведено критерій скінченності EWf(W). Основні твердження роботи узагальнюють деякі результати, отримані в дисертації Кульбуша, а також результати, відомі для процесів Гальтона-Ватсона. У процесі доведення досліджується існування f - моментів розв'язків деяких стохастичних різницевих рівнянь.